What is the Most Impressive Treatment to Foster Students’ Creative Thinking Skills? A Meta-Analysis and Bibliometric Review - Susilowati, Nur Endah; Muslim, Muslim; Efendi, Ridwan; Samsudin, Achmad (Universitas Islam Negeri Raden Intan Lampung, 2022)
Research related to learning treatment to train creative thinking skills has been frequently done. However, this has become a concern for teachers to assess which ‘learning treatment’ is better in developing students’ creative thinking skills. This study aims to analyze the most effective treatment in improving students’ creative thinking skills on science and mathematics concepts, based on data sources from international journal articles. The meta-analysis was conducted using CMA software and involving 21 published papers in international journal indexed by Scopus and or WOS. Data analysis was carried out by comparing the effect size values from the research results. According to the results of the meta-analysis, the average effect size data obtained with the learning model reached 1.075, the learning approach reached 1.627, and the learning media reached 1.575. Then based on the analysis, three ‘treatments’ were found that were considered as the most effective based on the effect size comparison, namely the PBL model with an effect size of 3.765, the STEM approach with an effect size of 0.90, and the use of interactive multimedia with an effect size of 0.83. The finding of this research stated that the PBL model is the most effective treatment to train students’ creative thinking skills. The results of this study provide views for science and mathematics educators to consider to use PBL (learning model), STEM/AM (learning approach), and technology-based learning media to train creative thinking.